Lâminas de irrigação e cobertura do solo na produção e qualidade de frutos da gravioleira - Da Silva, Raffael A. R.; Nunes, Járisson C.; De Lima Neto, Antonio J. [UNESP]; Cavalcante, Lourival F.; Da Silva, Maria R. M.; De Rodrigues, Rummenigge M. (Revista Brasileira de Ciencias Agrarias, 2013)
The crop of soursop has been known for presenting great potential for the domestic market and good prospects for export. In this context, an experiment was conducted in the municipality of Remigio in the state of Paraiba, in order to evaluate the effects of irrigation depths applied weekly on the productive behavior and postharvest quality of fruits of soursop 'Morada' in the soil with and without mulching with crop residues. Treatments were arranged in randomized blocks with three replications and three plants per plot, using a factorial arrangement 5×2, referring to the soil with and without mulching with crop residues, and five irrigation depths of 0, 4.3, 8.6, 12.9 and 17.2 mm plant1. Irrigation was performed manually, once a week from September 2008 to March 2009. The presence of mulch on the soil and increasing depths of irrigation elevated the values of mean mass, production per plant and yield of soursop 'Morada', and decreased the levels of soluble solids.
Irrigation depths and soil cover in production and quality ofsoursop fruits
Keywords: Annona muricata L; Irrigation; Mulching